Decentralized Composting of Food Waste: A Perspective on Scientific Knowledge - Sánchez, Antoni (Frontiers in Chemical Engineering, 2022)
Composting has been demonstrated to be an effective and sustainable technology to treat a wide variety of organic wastes. A particular aspect of composting is the number of technological options that can be used, from full-scale plants to small composters. In this sense, the interest in composting at home or on a community scale is exponentially growing in recent years, as it permits the self-management of organic wastes and obtaining compost that can be used by the same producer. However, some questions about the quality of the obtained compost or the environmental impact of home composting are still in an early stage of development and provide little knowledge. In this review, the main points related to home and community composting are analysed in detail according to the current scientific knowledge by highlighting their advantages and possible drawbacks. Particularly, the composting process performance is analysed, with temperature stratification being one of the main problems related to small amounts of organic matter. Simultaneously, compost quality is determined using parameters such as stability and/or maturity, concluding that home compost can be similar to industrial compost in both aspects. However, sanitisation of home compost is not always achieved. Regarding its environmental impact, gaseous emissions, especially greenhouse emissions, are the most studied category and are generally low. Finally, the effects of pandemics on home composting are also preliminary commented, concluding that this strategy can be a good alternative to have cities that are more resilient.